Construction and Validation of A Prognostic Model of Lung Adenocarcinoma Based on m5C Modification-Related Genes - Fan YANG; Nongyan WANG; Meng FANG; Yingjiao ZHANG; Haiyan HU; Peng FANG (Zhongliu Fangzhi Yanjiu)
ObjectiveTo construct a prognostic model of lung adenocarcinoma (LUAD) based on m5C modification-related genes and to explore its clinical value. MethodsBased on the LUAD data in TCGA, GSE30219, GSE31210, and GSE50081 cohorts, prognosis-related m5C modification-related genes were screened, and the prognostic model was constructed by using univariate Cox, Lasso, and multivariate Cox regression analyses. Kaplan-Meier curve, ROC curve, and Cox regression were used to observe the robustness and prognostic performance of the model. The correlation between the prognostic model and clinicopathologic features was further explored. ResultsA prognostic model consisting of eight m5C modification-related genes, including CDK1, CDKN1A, NOP2, RRM2, TCL6, TLR8, TRDMT1, and YTHDF2, was constructed. Risk score was an independent risk factor for the prognosis of patients with LUAD, and it is combined with age, T stage, and N stage to constitute a nomogram which can accurately predict the prognosis of patients. The infiltration of macrophages and CD4+/CD8+T cells was significantly reduced in high-risk patients. The risk score in LUAD tissues was significantly higher than that in normal tissues and was positively correlated with T stage and N stage. The risk score of smoking and EGFR wild-type patients was higher than that of non-smoking and EGFR-mutant patients. ConclusionThe prognostic model constructed based on m5C modification-related genes has shown good accuracy and stability in predicting the prognosis of patients with LUAD, and it is closely related to clinical features, driver gene mutations, and immune infiltration, which can provide a potential basis for the treatment and prognostic assessment of LUAD.